Guidelines for the Prevention of Teenage Pregnancy in Thailand: A Systematic Synthesis - คณฑา จิราจันทร์; โชติอำนวย ปิ่นแก้ว; ประสิทธิโชค วิภา; อินทมาศน์ อุษนันท์ (Ganesha Journal, 2019)
The objective of this research was to synthesize research systematically about guidelines for the prevention of teenage pregnancy in Thailand in cases of teenage pregnancy prevention and the effectiveness of guidelines for teenage pregnancy prevention in Thailand. Research was conducted by compiling research reports published in reliable academic databases from 2011-2016. Tools used in the systematic review included research screening form, research quality evaluation form, and the data extraction record form. The data was synthesized by analyzing general characteristics using descriptive statistics, classifying patterns of teenage pregnancy prevention and the effectiveness of using the teen pregnancy prevention model using the content brief. From this systematic review of research, it was found that there were 7 researches that could be analyzed and synthesized. There were 7 forms teenage pregnancy prevention in Thailand included; 1) the program to promote safe sexual intercourse, 2) health education program by applying motivation theory for disease prevention and social support, 3) unwanted pregnancy prevention program in teenage pregnancy, 4) empowerment training for student leaders on safe sexual behaviors and preventing unwanted pregnancy, 5) teenage pregnancy prevention pattern, 6) pattern of preventive action and premature pregnancy problems solving, and 7) pregnancy prevention pattern of early Thai female adolescents using the school as a base regarding the effectiveness of guidelines for preventing teenage pregnancy. The systematic review was found that knowledge, attitude and counseling skills, the belief about safe sex, preventing of sexually transmitted diseases and unwanted pregnancy and level of motivation to prevent risky sex behaviors after using teenage pregnancy prevention patterns were higher but there were 2 studies that had been formulated to prevent teen pregnancy but did not measure the effectiveness of the model.